Development and multicentric external validation of a prognostic COVID-19 severity model based on thoracic CT - Dirks, Ine; Bossa, Matías Nicolás; Berenguer, Abel Díaz; Mukherjee, Tanmoy; Sahli, Hichem; Deligiannis, Nikos; Verelst, Emma; Ilsen, Bart; Eyndhoven, Simon Van; Seyler, Lucie; Witdouck, Arne; Darcis, Gilles; et al. (BMC medical informatics and decision making, 2025)
Risk stratification of COVID-19 patients can support therapeutic decisions, planning and resource allocation in the hospital. In times of high incidence, a prognostic model based on data efficiently retrieved from one source can enable fast decision support.
Online veröffentlicht: 1. April 2025
Gesehen am 05.11.2025